NOWE ZASADY KONCESJONOWANIA DZIAŁALNOŚCI GOSPODARCZEJ - Trela, Anna (Wydział Prawa i Administracji UAM, 2002)
This article presents new legal solutions concerning licensing the performance of business activities regulated in the Polish Business Activity Law Act of 19 November 1999. At the beginning, the author defines the scope of licensing, pointing out its limitations in comparison with the previous state, and analysing regulations which define terms and conditions for making new licenses legally binding. She evaluates performing the duty imposed on the legislator in article 98 section 1 of the Polish Business Activity Law Act, which concerns defining in separate acts the scope and conditions for performing the business activity and the legal consequences o f a failure to fulfil this duty. A considerable part o f the article refers to such procedural issues as legal regulations concerning refusal to issue a license, a revocation or alteration of a license. The author evaluates these legal solutions, underlying the changes introduced by the legislator in comparison to the previously binding regulations. She analyses institutions that so far have been unknown in the license proceedings, such as the preliminary control institution and the administrative trial institution applied in a situation when the body intends to issue a limited number of licenses. She also points out solutions concerning the possibility to revoke a license. On the basis of an analysis of legal regulations as well as views presented in publications and judicial decisions, she characterizes legal decisions concerning licensing. The author pays a lot of attention to the position o f the licensing body in the license proceedings. Therefore, she analyses article 16 section 1 of the Polish Business Activity Law Act, according to which it is the licensing body that specifies the terms and conditions for performing a business activity which is subject to licensing. The author points out the differences between the act on business activity dated 1988 and the Polish Business Activity Law Act with respect to the way in which the licensing body is bound with the promise. Another issue discussed in the article concerns the validity of a license issued still before the Polish Business Activity Law Act came into force. At this point she also discusses licenses issued to civil partnerships.
NEW RULES OF LICENSING THE PERFORMANCE OF BUSINESS ACTIVITIES